2013
DOI: 10.11648/j.earth.20130203.11
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements and Health: An Environmental Risk in Nigeria

Abstract: Abstract:The concentration levels of trace elements in drinking water and food pose potential health risks to man and therefore require great attention. Studies on iodine deficiency disorders (IDD) indicate goiter prevalence in areas underlain by metamorphic Basement and Younger Granite rocks and its near absence in the sedimentary terrains. There are cases of dental fluorosis resulting from the excessive ingestion of fluoride in both children and adults living in both the crystalline and sedimentary terrains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In Zamfara where the gold bearing deposits contain unusually problematic concentration of lead and other heavy metals, the crushing of pebbles into sand in dry running flour mills produces enormous amounts of dust which in some places is highly contaminated with lead and possibly some other heavy metals (Nigeria Ministry of Mines and Steel Development, 2010) . Many researchershave shown the adverse impacts resulting from mining activities, like studies of Dubeet al, (2000), Ezigbo(2011) andLar (2013) to mention few. For example,pollution of mining industries in Brazil comes from gold mining activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Zamfara where the gold bearing deposits contain unusually problematic concentration of lead and other heavy metals, the crushing of pebbles into sand in dry running flour mills produces enormous amounts of dust which in some places is highly contaminated with lead and possibly some other heavy metals (Nigeria Ministry of Mines and Steel Development, 2010) . Many researchershave shown the adverse impacts resulting from mining activities, like studies of Dubeet al, (2000), Ezigbo(2011) andLar (2013) to mention few. For example,pollution of mining industries in Brazil comes from gold mining activities.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, series of studies has been conducted in the study area (Bagega) which is a rural area in Anka local government of Zamfara State (Nigeria). Most of these studies targeted the concentration and distribution pattern of heavy metals in soils (Adamuet al, 2011;Tsuwang et al, 2014;Yusuf et al, 2007), on water contaminations (Lar, 2013;Mark et al 2014;Majiyaet al 2015;), effect on health Dooyemaet al 2012;CDCP, 2012;Galadima, 2012), to mention few. But attempt has not been made in mapping out the spatial distribution of these elements in the study area (Bagega).…”
Section: Introductionmentioning
confidence: 99%
“…Alexander et al [10] conducted an extensive study on trace elements in groundwater sources within southern Nigeria and reported that most trace element concentrations complied with the WHO minimum concentration standard. However, the report might be typically applied to the country's southern region, while the situation is different in Nigeria's Northern parts.…”
Section: Introductionmentioning
confidence: 93%
“…Studies have shown that geochemical reference values are positively correlated with blood element content, and elements on Earth are closely related to life composition and health. [18] Lar and Uriah Alexander [19] studied the connection between trace elements in Nigeria 's crust and soil and water, and preliminarily analyzed their effects on human health. The correlation between them is very large, the influence of elements in the environment on the human body is very important.…”
Section: Prefacementioning
confidence: 99%